Intra-articular administration of adrenaline plus an irrigation pump system for visibility during the arthroscopic reconstruction of multiple knee ligaments without a tourniquet - Zhongyu, Xia; Zhen, Yu; Bingqing, Guo; Xintian, Kong; Meifeng, Guo; Jianda, Xu (Frontiers in Surgery, 2023)
Objective Multiple ligament knee injuries (MLKIs) are rare but severe systemic trauma. Single surgery in the acute setting is preferred, although with an extended operation time. To avoid the complications associated with a tourniquet, we herein describe a method for visibility without a tourniquet: intra-articular administration of adrenaline plus an irrigation pump system. Study design This is a cohort study with a level of evidence of 3. Methods From April 2020 to February 2022, 19 patients with MLKIs were reviewed retrospectively. All patients got intra-articular administration of adrenaline plus an irrigation pump system for visibility without a tourniquet. The following parameters were assessed: visibility, range of motion, knee stability, visual analog scale (VAS) score, range of motion (ROM), Lysholm score, Tegner activity level, and International Knee Documentation Committee Subjective Knee Form (IKDC). Results All patients were followed up for at least 6 months. At the latest follow-up, the mean VAS score, ROM, Lysholm score, and IKDC were 1.79 ± 0.86, 121.21 ± 10.96, 88.16 ± 5.21, and 88.53 ± 5.06, respectively. The average Tegner activity level decreased significantly from preinjury to postoperation (5.16 ± 0.83 vs. 3.11 ± 0.88, P < 0.001). Of the 19 patients, 17 (89.47%) had good knee function, while only two patients (10.53%) had asymptomatic knees with positive Lachman tests. A total of 17 patients (89.47%) had good or excellent visualization during arthroscopy. Of the 19 patients, three (15.79%) required an increased fluid pressure to achieve a clear operative view. Two patients converted to tourniquet inflation due to persistent intra-articular bleeding after using shavers. Conclusions The intra-articular administration of adrenaline plus an irrigation pump system is recommended as an alternative to a tourniquet to achieve a good visual field. Further evidence-based work with a larger sample is needed.